Breastfeeding, the use of docosahexaenoic acid-fortified formulas in infancy and neuropsychological function in childhood. Issue 3 (4th February 2010) - Gale, Catharine R; Marriott, Lynne D; Martyn, Christopher N; Limond, Jennifer; Inskip, Hazel M; Godfrey, Keith M; Law, Catherine M; Cooper, Cyrus; West, Carolyn; Robinson, Siân M
Abstract : Objective: To investigate the relation between breastfeeding, use of docosahexaenoic acid (DHA)-fortified formula and neuropsychological function in children. Design: Prospective cohort study. Setting: Southampton, UK. Subjects: 241 children aged 4 years followed up from birth. Main outcome measures: IQ measured by the Wechsler Pre-School and Primary Scale of Intelligence (3rd edn), visual attention, visuomotor precision, sentence repetition and verbal fluency measured by the NEPSY, and visual form-constancy measured by the Test of Visual-Perceptual Skills (Non-Motor). Results: In unadjusted analyses, children for whom breast milk or DHA-fortified formula was the main method of feeding throughout the first 6 months of life had higher mean full-scale and verbal IQ scores at age 4 years than those fed mainly unfortified formula. After adjustment for potential confounding factors, particularly maternal IQ and educational attainment, the differences in IQ between children in the breast milk and unfortified formula groups were severely attenuated, but children who were fed DHA-fortified formula had full-scale and verbal IQ scores that were respectively 5.62 (0.98 to 10.2) and 7.02 (1.56 to 12.4) points higher than children fed unfortified formula. However, estimated total intake of DHA in milk up to age 6 months was not associated with subsequent IQ or with score on any other test. Conclusions: Differences in children's intelligence according to type of milk fed in infancy may be due more to confounding by maternal or family characteristics than to the amount of long-chain polyunsaturated fatty acids they receive in milk.